‘Behind the Back of Visible History’. Understanding, Explaining and Narrating Lepanto - Campailla, Carlo (E|C, 2024)
This article aims to examine the significance that an event such as battle can assume within historical discourse, focusing in particular on the relationship between historical structures and events. Analyzing a case of historical disclosure of the battle of Lepanto, we propose to verify the hypothesis that the explanation of an event depends on the different deep dimensions of history, that it is the task of the historian to rebuild and from which the ideological presuppositions of the historian can be deduced. In this way, in the analyzed text a frontier is drawn between a superficial explanation and a thorough one. Analyzing, then, the enunciative strategies used in this text, we will finally focus on possible strategies of historical dissemination, and on how certain needs of divulgation guide the construction of the historical fact.